Foraging Behavior of Apis mellifera L. Landraces Under Terai Condition of Nepal - Parajuli, Sangita egan; Thapa, RB (Nepal Journal of Science and Technology, 2013)
A study was conducted to compare the foraging behavior of landraces of Apis mellifera L. under Terai condition of Nepal, for which the honeybee colonies were brought from Dang, Chitwan, Sarlahi and Parsa districts. The experiment was laid out in a randomized complete block design (RCBD) with six replications (colonies) and four treatments (landraces), i.e. Apis mellifera carnica, Apis mellifera russian, Apis mellifera buckfast and Apis mellifera ligustica. Each experimental unit consisted of 10 frame Langstroth bee hives with about 50,000 workers. Data recording continued from 26 March to 14 July in Chitwan. The landrace A.m. buckfast had the highest out-going foragers/5min (115.667 workers/ colony) significantly higher than A.m. carnica (73.500 workers/colony), A.m. russian (52.667 workers/colony) and A.m. ligustica (48.667 workers/colony), respectively. Similarly, the average number of foragers (in-coming with nectar/5min) was recorded the highest in A.m. buckfast (104.501 workers/colony) which was 1.46, 1.63, 1.78 times higher than A.m. carnica, A.m. russian, A.m. ligustica, respectively. Therefore, A.m. buckfast and A.m. carnica colonies were the best performers in relation to foraging behavior among the four evaluated land races during spring and summer seasons under Terai condition of Nepal. Nepal Journal of Science and Technology Vol. 13, No. 2 (2012) 51-56 DOI: http://dx.doi.org/10.3126/njst.v13i2.7714